Features of the mental state of internally displaced persons with obsessive-compulsive disorder - Grynevych, Євгенія (Psychosomatic Medicine and General Practice, 2024)
Relevance. Combat actions and the impact of their immediate threat are currently a significant factor in the deterioration of mental health for citizens of Ukraine. Under the constant influence of stress factors, not only new mental illnesses develop, but also exacerbation and aggravation of already existing mental disorders arise. Deterioration of the mental health of internally displaced persons with OCD can lead to their complete disability, and therefore monitoring the mental state of such patients in conditions of combat actions is critically necessary. Aims. The purpose of the study was to establish the features of the mental state of internally displaced persons with obsessive-compulsive disorder. Materials and methods. 48 patients with a diagnosis of OCD who were internally displaced persons and 50 people with a diagnosis of OCD who were not internally displaced persons were examined. Manifestations of anxiety and depression were assessed using the Hospital Anxiety and Depression Scale (HADS). The level of severity of obsessions and compulsions was determined using the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS). The level of quality of life was determined using the Quality of Life Assessment Scale (CQLS) (Chaban O.S., 2017). Results. As a result of the study of the mental state of patients with OCD, it was found that the intensity of symptoms of the obsessive-compulsive spectrum, and therefore the severity of the course of OCD in both groups, was moderate and did not have statistically significant differences. However, it was found that in the group of internally displaced persons with OCD, a significantly higher level of anxiety and depressive symptoms was observed, as well as a significantly lower level of quality of life. This suggests that although the internal displacement does not lead to a deterioration in the course of OCD due to an increase in the intensity of obsessive-compulsive symptoms, the mental state of such patients deteriorates due to a pronounced impregnation with anxiety and depressive symptoms, which leads to a significant decrease in their quality of life.